Spatial statistics with S-Plus: Available libraries and functions - Tillmann Krahnke (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
An overview is given over the S-Plus libraries and modules for statistical analysis of spatial data that are currently available at the Department of Statistics, University of Dortmund. It is believed that this includes all libraries currently available on the internet. Listings of functions show what statistical techniques are implemented, and where to find them. This facilitates the search for any particular function, and saves from re-programming of techniques that are already available. This overview may there- fore also be viewed as a starting point for developing further analysis tools for spatial and spatio-temporal statistics in S-Plus.
Keywords: 519; Geostatistics; lattice data; modules; public libraries; S-Plus; spatial statistics; spatial point pattern